Imaging Findings in Neonates With Congenital Pyriform Sinus Fistula: A Retrospective Study of 45 Cases - Li, Li; Zhao, Dong-Ji-Hui; Yao, Tao-Yue; Xiang, Yong-Hua; Liu, Hong; Ma, Qiu-Hong; Jin, Ke; He, Si-Ping (Frontiers in Pediatrics, 2021)
Background:Congenital pyriform sinus fistula (CPSF) is a rare branchial cleft deformity. The characteristics and management of CPSF in neonates are different from those in children or adults, and a sufficient understanding of the imaging features of neonatal CPSF can facilitate its preoperative diagnosis. Thus, the aim of this study was to investigate the ultrasonography(US) and computed tomography(CT) imaging findings of congenital pyriform sinus fistula(CPSF) in neonates. Methods:Forty-five full-term neonates with CPSF, confirmed by pathology after surgical resection from January 2012 to October 2020, were included in this retrospective study. All patients underwent preoperative cervical US examination and contrast-enhanced CT scan, and the imaging findings were reviewed. Results:Forty-six cervical cystic masses were found in 45 neonates with CPSF, including 1 case with bilateral lesions, 3 cases with lesions on the right side, and 41 cases on the left side. Both US and CT detected neck abnormality among all cases, but the diagnostic accuracy rate of US (15/46) was below that of CT (42/46). Moreover, CT showed significantly higher detection rates of the air-bubbles within lesions, the involvement of the ipsilateral thyroid, deviation of the airway, and expansion into the mediastinal and retropharyngeal space compared to the US. As the age increased, it was more likely to present absence of air-containing, thick cyst wall, and poorly-defined border (Ρ< 0.05). Conclusion:CPSF in the neonates showed distinctive imaging findings on contrast-enhanced CT scans, which provides important supplementary information for the diagnosis of CPSF after the initial US examination.